1996
DOI: 10.1074/jbc.271.42.26194
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Is Required for Regulation of Glucose-stimulated Insulin Secretion in a Mouse Pancreatic Beta Cell Line, MIN6

Abstract: To determine whether mtDNA and mitochondrial respiratory function in pancreatic beta cells are necessary for the phenotypic expression of glucose-stimulated insulin secretion, we used a cultured mouse pancreatic beta cell line, MIN6, and two derivative lines, mtDNA knockout MIN6 ( 0 MIN6) and mtDNA repopulated cybrid MIN6. The MIN6 cells retain the property of glucose-stimulated insulin secretion, but their mtDNA knockout induced the loss of mitochondrial transcription, translation, and respiration activity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 43 publications
11
86
0
1
Order By: Relevance
“…Thus the chemical elimination of mitochondrial DNA leads to complete inhibition of glucose-stimulated insulin secretion [26]. Some experiments have, however, shown that formation of cybrids between enucleated donor cells containing normal mitochondria and r 0 cells of the mouse beta-cell line MIN6 permitted restoration of glucose-induced insulin secretion [70]. These experiments thus unequivocally show the pivotal role of the mitochondria in glucose-stimulated insulin secretion.…”
Section: Beta-cell Model Of Mitochondrial Diabetesmentioning
confidence: 70%
“…Thus the chemical elimination of mitochondrial DNA leads to complete inhibition of glucose-stimulated insulin secretion [26]. Some experiments have, however, shown that formation of cybrids between enucleated donor cells containing normal mitochondria and r 0 cells of the mouse beta-cell line MIN6 permitted restoration of glucose-induced insulin secretion [70]. These experiments thus unequivocally show the pivotal role of the mitochondria in glucose-stimulated insulin secretion.…”
Section: Beta-cell Model Of Mitochondrial Diabetesmentioning
confidence: 70%
“…29 Depletion of mtDNA in MIN6 cells resulted in loss of ability to release insulin by glucose stimulation which was restored by introduction of mtDNA into the knockout cells. 30 Thus high glucose exposure induced reduction in the expression of mitochondrial aconitase may result in Table 1 were incubated for 60 minutes. Immediately after incubation, aliquots of the medium were removed for assay of insulin by RIA as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 0 line isolated from the mouse pancreatic beta cell line MIN6 was used for studying the influence of mtDNA depletion and its repopulation on phenotypic expression of glucose-stimulated insulin secretion (27).…”
Section: Discussionmentioning
confidence: 99%
“…A mouse pancreatic beta cell line (MIN6) was cultivated as described previously (27) Isolation of 0 Mouse Cells-Cells were plated at 1 ϫ 10 2 -5 ϫ 10 4 cells/dish, and beginning 24 h after plating they were treated with ditercalinium (DC, an antitumor bis-intercalating agent) for 1 month. C2 and NIH3T3 cells were treated with 1.5 g/ml DC, while MIN6 cells were treated with 56 ng/ml DC.…”
Section: Methodsmentioning
confidence: 99%